(untitled) (Fiep Bulletin - online, 2013)
This is a reflection on ethical relations in the context of a technological health care setting. Its purpose is to analyze the historical evolution of science and technology in Latin America, specifically in Brazil, with a focus on the existing clash between technical and scientific development and the ethical perspective. The emphasis is on the risks of the culture of objectivity that has gradually been dominating the post-modern world, placing the machine over man and restricting the expression of human subjectivity. The grandeur of technology ends up by enchanting everybody, limiting the critical vision of daily practice and contributing to banalizing the pain of others. On the other hand, the diversification of principles (social, religious, political) makes it difficult to find equilibrium between individual freedom, collective aspirations and the democratic and equanimous application of the advances made by science and technology. From this perspective, the education of health professionals deserves special attention on the part of all educators in the field for having a multidisciplinary dialog in favor of life as a declaration of bioethics. Finally, we are warned that, when faced with the contradictions and paradoxes of the world, if we do not build and cultivate an ethical culture we run the risk of being carried with the enchantment and benefits of progress that, to a great extent, run against the current of life. However, it’s not about simply being critical about progress, but about what symbolizes only technical and economical advances without ethical considerations.